Does Immigration Decrease Far-Right Popularity? Evidence from Finnish Municipalities - Jakub Lonsky (Global Labor Organization (GLO), 2020)
Across Europe, far-right parties have made significant electoral gains in recent years. Their anti-immigration stance is considered one of the main factors behind their success. Using data from Finland, this paper studies the effect of immigration on voting for the far-right Finns Party on a local level. Exploiting a convenient setup for a shift-share instrument, I find that one percentage point increase in the share of foreign citizens in municipality decreases Finns Party's vote share by 3.4 percentage points. Placebo tests using pre-period data confirm this effect is not driven by persistent trends at the municipality level. The far-right votes lost to immigration are captured by the two pro-immigration parties. Turning to potential mechanisms, immigration is found to increase voter turnout, potentially activating local pro-immigration voters. Moreover, the negative effect is only present in municipalities with high initial exposure to immigrants, consistent with the intergroup contact theory. Finally, I also provide some evidence for welfarestate channel as a plausible mechanism behind the main result.
Keywords: H71; J15; J61; P16; 330; Immigration; far-right; political economy; voting